Assessment of nicotine addiction risk and challenges to stopping smoking among ankylosing spondylitis patients - Büyükavcı, Raikan; Aktürk, Semra; Aktürk, Ümmühan (Journal of Dependence, 2025)
Objective: Smoking is a risk factor for rheumatic diseases. The objective of this study was to evaluate the relationship between high nicotine addiction risk and disease activity in patients with ankylosing spondylitis (AS) and the level of addiction risk and difficulty in quitting smoking. Method: This was a cross-sectional study. A total of 65 patients diagnosed with AS were included in the study between November 2022 and September 2023. The following instruments were utilized: a patient identification form, the Bath Ankylosing Spondylitis Disease Activity Index, the Ankylosing Spondylitis Quality of Life Questionnaire, the Fagerström Nicotine Dependence Index, and the Challenges to Stopping Smoking. Results: The results indicated that 36 patients (55.4%) exhibited moderate to severe nicotine addiction risk. The disease activity of 50 patients (77%) was found to be moderate to high, and these patients exhibited high smoking addiction risk scores and low quality of life scores. Among all patients, 42 (65%) expressed willingness to quit smoking, but this was significantly more challenging in those with moderate-high disease activity. Conclusion: Smoking is one of the modifiable factors thought to influence disease activity in AS. Although quitting smoking is among the treatment recommendations in the treatment of AS, a significant portion of smokers (approximately two-thirds) are unable to quit smoking due to nicotine addiction, despite their desire to do so.